The Globalization of Cultural Eutrophication in the Coastal Ocean: Causes and Consequences - Malone, Thomas C.; Newton, Alice (Frontiers in Marine Science, 2020)
Coastal eutrophication caused by anthropogenic nutrient inputs is one of the greatest threats to the health of coastal estuarine and marine ecosystems worldwide. To better understand and manage this threat, we compared six contrasting coastal ecosystems that are subjected to a range of riverine inputs of freshwater (buoyancy) and nutrients to address (i) impacts of anthropogenic nutrient inputs on ecosystem services; (ii) how ecosystem traits minimize or amplify these impacts; (iii) synergies among pressures (nutrient enrichment, over fishing, coastal development, and climate-driven pressures in particular); and (iv) management of nutrient inputs to coastal ecosystems. Globally, ~ 24% of the anthropogenic N released in coastal watersheds is estimated to reach coastal ecosystems. Our comparative assessment revealed that (i) in terms of the spatial extent of habitat degradation, Chesapeake Bay ranks number one followed in rank order by the northern Gulf of Mexico, the Baltic Sea, Great Barrier Reef, East China Sea and the northern Adriatic Sea; (ii) impacts of increases in anthropogenic nutrient loading are, and will continue to be, exacerbated by synergies with other pressures including over fishing, coastal development and climate-driven increases in sea surface temperature, acidification and rainfall; and (iii) when defined in terms of quantitative ranges of primary production, trophic status is not useful for relating anthropogenic nutrient loading to impacts. While managed reductions in point source inputs from sewage treatment plants are increasingly successful, controlling inputs from diffuse sources remains a challenging problem. Thus, it is likely that the severity of coastal eutrophication will continue to increase in the absence of effectively enforced, ecosystem-based management of both point and diffuse sources of nitrogen and phosphorus. This requires sustained, integrated research and monitoring, as well as repeated assessments of nutrient loading and impacts. These must be informed and guided by ongoing collaborations among scientists, politicians, managers and the public.